Chicana/o Remix : Art and Errata Since the Sixties - Davalos, Karen Mary, 1964- (Book collections on Project MUSE., 2017)
'Chicana/o Remix' casts new light not only on artists - such as Sandra de la Loza, Judy Baca, and David Botello, among others - but on the exhibitions that feature their work, and the collectors, curators, critics, and advocates who engage it.